Molecular imaging of immune checkpoints in oncology: Current and future applications. (1st November 2022) - Ge, Shushan; Jia, Tongtong; Li, Jihui; Zhang, Bin; Deng, Shengming; Sang, Shibiao
Abstract: Immune checkpoint (IC) blockade therapy has become the first-line treatment for various cancers. However, the low response rate and acquired drug resistance severely restrict the clinical application of immune checkpoint inhibitors (ICIs). Nuclide molecular imaging of ICs can provide non-invasive and whole-body visualization of in vivo IC dynamic biodistribution. Therefore, molecular imaging of ICs can predict and monitor responses to ICIs as a complementary tool to existing immunohistochemical techniques. Herein, we outlined the current status and recent advances in molecular imaging of the "first-generation" and "next-generation" ICs in preclinical and clinical studies. Highlights: Blockade of immune checkpoints such as CTLA-4 and PD-1/PD-L1 has dramatically changed clinical oncology over the past decade. Molecular imaging allows non-invasive, quantitative and repetitive assessment of immune checkpoints distribution in vivo. Noninvasive imaging of immune checkpoints can guide cancer immunotherapy into the era of precision medicine. We focused on the molecular probes used in preclinical and clinical PET/SPECT imaging studies targeting immune checkpoints.